2007
DOI: 10.2353/ajpath.2007.070471
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Apelin-Apelin Receptor System for Oxidative Stress-Linked Atherosclerosis

Abstract: The recently identified endogenous peptide apelin and its specific apelin receptor (APJ) are currently being considered as potential regulators in vascular tissue. Previously, we reported apelin mediates phosphorylation of myosin light chain and elicits vasoconstriction in vascular smooth muscle. In this study, physiological roles of the apelin-APJ system were investigated on atherosclerosis. In APJ and apolipoprotein E double-knockout (APJ ؊/؊ ApoE ؊/؊ ) mice fed a high-cholesterol diet, atherosclerotic lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
5
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 35 publications
6
85
5
1
Order By: Relevance
“…In our study, the dyslipidaemia remained unchanged with CPAP therapy and therefore contributed insignificantly to the changes reported in apelin levels. However, the APJ/apelin system appears to have a role in the development of hypercholesterolaemia-associated atherosclerosis (Hashimoto et al 2007). Therefore, although elevated plasma apelin levels in untreated OSA may be beneficial in terms of glucose homeostasis (and hypertension -see below), there are putative deleterious consequences for oxidative stress-linked vascular disease, which warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the dyslipidaemia remained unchanged with CPAP therapy and therefore contributed insignificantly to the changes reported in apelin levels. However, the APJ/apelin system appears to have a role in the development of hypercholesterolaemia-associated atherosclerosis (Hashimoto et al 2007). Therefore, although elevated plasma apelin levels in untreated OSA may be beneficial in terms of glucose homeostasis (and hypertension -see below), there are putative deleterious consequences for oxidative stress-linked vascular disease, which warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…More recent reports have indicated that this peptide has been down-regulated in subjects with acute heart failure (5). Furthermore, apelin also induced vascular smooth muscle cell proliferation, which was inhibited by superoxide dismutase or diphenylene iodonium; APJ deficiency is preventative against oxidative stress-linked atherosclerosis; the apelin-APJ system is a mediator of oxidative stress in vascular tissue (6), and thus we speculated it to have some relationship with arterial atherosclerosis. …”
Section: Apelin Is a Peptide Recently Isolated From Bovine Stomach Exmentioning
confidence: 98%
“…The role of leptin in atherogenesis is currently controversial as leptin (ob/ob) or leptin receptor (db/db) deficiency in Apoe −/− mice has resulted in attenuation of plaque formation [53] or increased atherogenesis [54]. Inactivating of the apelin receptor (APJ) in Apoe −/− mice resulted in reduced lesion size and oxidative stress, suggesting a role for apelin in atherogenesis [55].…”
Section: Adiponectin and Other Adipokinesmentioning
confidence: 99%